Penerapan PSAK 65 Dalam Penyusunan Laporan Keuangan Konsolidasian Pada PT Dalimo Jaya Motor - Sri Wulan Saputri; Bunga Puji Lestari; Vania Adisty Hasibuan; Siti Rodiah (Jurnal Publikasi Ilmu Manajemen, 2023)
This research focuses on the phenomenon that occurred at PT Dalimo Jaya Motor, a workshop business in Marpoyan Damai District, Pekanbaru City, which has been operating for about 7 years and has prepared financial statements based on Statement of Financial Accounting Standards 65 (PSAK 65). This study aims to see the application of preparing financial statements based on PSAK 65. In this study, researchers used a qualitative approach with a descriptive method, the type of data collected consisted of primary data taken directly from the efforts of PT. Dalimo Jaya Motor's. Data collection techniques are used by conducting interviews and documentation. The results showed that the company was in accordance with the applicable standard, namely PSAK 65.